O-007 Upss (utilization of proper imaging or screening for strokes) study. (23rd July 2017) - Teleb, M; Toe, W; Ianotti, J Lee
Abstract : Introduction/Purpose: Identification of large vessel occlusion (LVO) strokes has become increasingly important with the recent publications of five favorable acute stroke thrombectomy trials. Delay in time to treatment has been shown to hinder outcomes. Identification of (LVO) can be done with LVO screening tools or with early CTA allowing for timely activation of transfer and Neuroendovascular evaluation. We evaluated four primary stroke centers (PSCs) one year after American Stroke Association guidelines on thrombectomy are published. Methods: Data on LVO screening, time to CTA from Stroke alert, time to official CTA read, transfer times, as well as NIHSS were collected by our stroke center coordinators. Data for all patients with NIHSS>=6 were evaluated for the first nine months of 2016 after approval by IRB. Results: In this cohort of 4 PSCs without Neuroendovascular services, LVO screening was not consistently done in all patients, 0% had formal screening. 37% of patients with NIHSS>=6 eventually had CTA. Only 10% of CTAs where read within one hr. Of patients eventually transferred, 17% were within 2 hours. Conclusion: Despite new guidelines, patients with NIHSS>=6 are not consistently screened, CTA interpretation is significantly delayed, and only 17% are being transferred within 2 hours. We recommend that Stroke and Neurovascular organizations should have get with the guidelines campaign for mandatory LVO screening in ED, time to CTA, time to CTA read, and time to transfer to comprehensive stroke centers. Disclosures: M. Teleb: None. W. Toe: None. J. Lee Ianotti: None.